Probing the transient evolution and heat transfer of nascent liquid film during initial condensation. (15th September 2022) - Wei, Xiang; Wu, Chun-Mei; Mo, Dong-Ming; Li, You-Rong
Highlights: Transient evolution of nascent liquid film during initial condensation is studied Three stages are recognized by interfacial mass flux from adsorption to condensation The heat and mass fluxes determined by two independent methods show good agreement Abstract: A hybrid theoretical and simulation method is employed to investigate the transient characteristics of heat and mass transfer of nascent liquid film during initial condensation of argon vapor on a subcooled substrate. The method combines a non-equilibrium thermodynamics analysis with molecular dynamics simulations to provide the kinetics and evolution of the atoms. Throughout the evolution process, three different stages can be recognized by the variation of interfacial mass flux. Initially, the solid-vapor interfacial effect is dominated and the argon atoms are adsorbed as clusters and aggregate on the surface. In the transition stage, the mass flux increases and the adsorption behavior almost vanishes, a nascent liquid-like film is formed. When the times exceed a critical value of t c, the condensation process is initiated and the solid-vapor interface is replaced by the vapor-liquid interface. As a result, the mass flux keeps constant. During the adsorption process, the driven force of is theoretical determined through the cluster evolutions. With the decrease of cooling temperature, the mass flux is enlarged and the time for the transition becomes earlier. The mass flux determined from MD simulations coincides well with the theoretical analysis from statistical rate theory. Meanwhile, the spatial evolutions of the atoms are also traced. The atoms in the near wall region present a crystal-like structure. Compared with that in bulk vapor phase, the atoms in the liquid film have a stronger mobility. For the heat and mass transportation, the interfacial temperature jump and the thermal resistance is increased with the increase of cooling temperature. Two independent methods are adopted to obtain the heat and mass fluxes. The slop of the relationship between the heat and mass fluxes shows close agreement with the latent heat of argon, which reveals the occurrence of condensation.